Interrelated Analysis of Performance and Fouling Behaviors in Forward Osmosis by Ex-Situ Membrane Characterizations - Aydiner, Coskun; Topcu, Semra; Tortop, Caner; Kuvvet, Ferihan; Ekinci, Didem; Dizge, Nadir; Keskinler, Bulent (IntechOpen, 2012)
None